Molecular Mechanisms of Increased Platelets: An In Silico of the Active Compounds in Psidium guajava (Biosaintifika: Journal of Biology & Biology Education, 2024)
Dengue virus infection causes thrombocytopenia. Psidium guajava is widely used by people to increase platelet counts. This research aims to analyze in silico the molecular mechanisms of compounds in guava fruit in increasing platelets. The compounds in guava fruit were taken from Dr. Duke's Phytochemical and Ethnobotanical Databases, which include secondary metabolites such as flavonoids, terpenoids, tannins, alkaloids, and fatty acids. Target proteins were predicted using PharmMapper. Protein interaction networks were created using STRING, visualized, and analyzed using Cytoscape. Potential target proteins were identified by topology, modularity, functional, and KEGG pathway analysis. Degree and betweenness centrality are parameters in topological analysis and the cluster with the highest score is selected as the functional module. The results showed that MAPK1, MAPK14, and AKT1 are involved in many inflammatory pathways, and MMP9 is a target protein directly involved in increasing vascular permeability. The compounds arjunolic acid, farnesene, beta-carotene, and alpha-linolenic acid inhibit MAPK1, citral, ellagic acid, palmitic acid, and oleanolic acid inhibit MAPK14, guaijaverin, pantothenic acid, and citric acid inhibit AKT1, guaijaverin and pantothenic acid inhibit MMP9. It was concluded that the bioactive compounds in guava fruit play a role in increasing platelets by inhibiting the MAPK, PI3K-Akt pathways, and leukocyte trans-endothelial migration, thereby inhibiting or reducing the production and expression of inflammatory mediators and vascular permeability.